2020
DOI: 10.1371/journal.pone.0241850
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammatory signaling by the ST6Gal-I sialyltransferase

Abstract: The ST6Gal-I sialyltransferase, an enzyme that adds α2-6-linked sialic acids to N-glycosylated proteins, regulates multiple immunological processes. However, the contribution of receptor sialylation to inflammatory signaling has been under-investigated. In the current study, we uncovered a role for ST6Gal-I in promoting sustained signaling through two prominent inflammatory pathways, NFκB and JAK/STAT. Using the U937 monocytic cell model, we determined that knockdown (KD) of ST6Gal-I expression had no effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Diabetics are at an increased risk of developing HFS and we confirmed an association for ST6GAL1 with T2D, and also found that rs6783836 was associated with glycated haemoglobin levels, a marker routinely used in the diagnosis and monitoring of diabetes, supporting an interrelationship. ST6GAL1 has a known role in inflammation 31 and we found an association between rs6783836 and lymphocyte count and psoriasis. Given that others have associated ST6GAL1 with psoriasis in an Asian population, 32 these data support a link between these syndromes and an underlying defect in the inflammatory pathway.…”
Section: Discussionsupporting
confidence: 50%
“…Diabetics are at an increased risk of developing HFS and we confirmed an association for ST6GAL1 with T2D, and also found that rs6783836 was associated with glycated haemoglobin levels, a marker routinely used in the diagnosis and monitoring of diabetes, supporting an interrelationship. ST6GAL1 has a known role in inflammation 31 and we found an association between rs6783836 and lymphocyte count and psoriasis. Given that others have associated ST6GAL1 with psoriasis in an Asian population, 32 these data support a link between these syndromes and an underlying defect in the inflammatory pathway.…”
Section: Discussionsupporting
confidence: 50%
“…These opposing functions of protein sialylation depend upon the target substrate molecules and the locations where the modification is regulated. Recent studies in mice using BM transplantation or monocyte-specific Cre-LoxP system have uncovered the key function of neuraminidases and sialyltransferases in monocytes and macrophages ( 80 , 90 , 94 , 120 , 123 ). More studies are needed to address the importance of protein sialylation using mice with additional tissue- and cell-type-specific targeting of the machinery, including endothelial cells and vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Holdbrooks et al. showed that BM-derived macrophages from mice with myeloid-specific St6Gal1 deletion display reduced long-term activation of nuclear factor kappa B (NF-kB) by TNFα or lipopolysaccharide (LPS) ( 120 ). Furthermore, in experiments using cultured monocytes, the study implicates TNFR1 or TLR4 to be a potential substrate of St6Gal1-mediated α2-6 sialylation related to the inflammatory regulation by monocytes/macrophages.…”
Section: Mouse Models Of Sialylation and Atherosclerosismentioning
confidence: 99%
“…Although ST6Gal1 is thought to be the main enzyme responsible for the bulk of N-glycoprotein-linked a2-6 sialylation, mice with total St6gal1 knockout are viable, with a surprisingly mild phenotype mainly manifest in immune cell function: increased inflammation, defects in dendritic cell, and myelopoiesis, as well as mature B-cell development (50)(51)(52). Also, the phenotype of mice with specific knockout of St6gal1 in the liver, an organ with particularly high ST6Gal1 expression, is mild (32).…”
Section: St6gal1 a Non-essential Protein With Unique Enzymatic Activi...mentioning
confidence: 99%